Solid Lipid Nanoparticles: Review of the Current Research on Encapsulation and Delivery Systems for Active and Antioxidant Compounds - Edy Subroto; Robi Andoyo; Rossi Indiarto (MDPI AG, 2023)
Various active compounds are easily damaged, so they need protection and must be easily absorbed and targeted. This problem can be overcome by encapsulating in the form of solid lipid nanoparticles (SLNs). Initially, SLNs were widely used to encapsulate hydrophobic (non-polar) active compounds because of their matched affinity and interactions. Currently, SLNs are being widely used for the encapsulation of hydrophilic (polar) and semipolar active compounds, but there are challenges, including increasing their entrapment efficiency. This review provides information on current research on SLNs for encapsulation and delivery systems for active and antioxidant compounds, which includes various synthesis methods and applications of SLNs in various fields of utilization. SLNs can be developed starting from the selection of solid lipid matrices, emulsifiers/surfactants, types of active compounds or antioxidants, synthesis methods, and their applications or utilization. The type of lipid used determines crystal formation, control of active compound release, and encapsulation efficiency. Various methods can be used in the SLN fabrication of active compounds and hydrophilic/hydrophobic antioxidants, which have advantages and disadvantages. Fabrication design, which includes the selection of lipid matrices, surfactants, and fabrication methods, determines the characteristics of SLNs. High-shear homogenization combined with ultrasonication is the recommended method and has been widely used because of the ease of preparation and good results. Appropriate fabrication design can produce SLNs with stable active compounds and antioxidants that become suitable encapsulation systems for various applications or uses.